Interferon Kappa Is Important for Keratinocyte Host Defense against Herpes Simplex Virus-1 - Yuanyuan Li; Yueqi Song; Leqing Zhu; Xiao Wang; Brittany Richers; Donald Y. M. Leung; Lianghua Bin (Journal of Immunology Research)
Type I interferon kappa (IFNκ) is selectively expressed in human keratinocytes. Herpes simplex virus-1 (HSV-1) is a human pathogen that infects keratinocytes and causes lytic skin lesions. Whether IFNκ plays a role in keratinocyte host defense against HSV-1 has not been investigated. In this study, we found that IFNκ mRNA expression was induced by addition of recombinant IFNκ and poly (I:C); and its expression level was significantly greater than IFNa2, IFNb1, and IFNL1 in both undifferentiated and differentiated normal human epidermal keratinocytes (NHEKs) under resting and stimulation conditions. Although IFNe was expressed at a relatively higher level than other IFNs in resting undifferentiated NHEK, its expression level did not change after stimulation with recombinant IFNκ and poly (I:C). HSV-1 infection inhibited gene expression of IFNκ and IFNe in NHEK. Silencing IFNκ in NHEK led to significantly enhanced HSV-1 replication in both undifferentiated and differentiated NHEK compared to scrambled siRNA-transfected cells, while the addition of recombinant IFNκ significantly reduced HSV-1 replication in NHEK. In addition, we found that IFNκ did not regulate protein expression of NHEK differentiation markers. Our results demonstrate that IFNκ is the dominant type of IFNs in keratinocytes and it has an important function for keratinocytes to combat HSV-1 infection.